Reconfigurable, Multi-Material, Voxel-Based Soft Robots - Legrand, Julie; Terryn, Seppe; Roels, Ellen; Vanderborght, Bram (IEEE robotics and automation letters, 2023)
Voxel-based robots are aggregations of soft and simple building blocks that have been extensively evolved and simulated to perform various tasks, like walking, jumping or swimming. However, real-life voxel-based robots are rather scarce because of their challenging design and assembly. With the current materials and assembling methods, the interfaces between the soft multi-material voxels are prone to failure. This work proposes to make voxels out of reversible Diels-Alder polymers, which are available in a broad range of mechanical properties. By doing so, the covalent bonds at the multi-material interface ensure strong chemical connections, while allowing for reconfiguration. A first voxel-based gripper is thus robustly assembled, then disassembled, using its pieces (voxels) for reassembling another robot, i.e. a voxel-based walking robot. This reconfigurable property allows iterative validation of the simulated voxel-based robots and fine-tuning of the simulations parameters in a sustainable and economical way. Both physical voxel-based robots show similar behaviors as their simulations with root-mean-square errors down to 10.4%.